Socio-Economic Characteristics and Animal Feed Resources of Ruminant Farmers in Katsina State, Nigeria - A. Aruwayo; K.S. Ahmed; I.R. Muhammad (Journal of Applied Sciences and Environmental Management)
: The survey was conducted to identify common ruminant feed resources in and around Dutsin-ma, Sheme, Faskari in Katsina state and investigate the socio-economic characteristics of ruminant farmers, farming system, feed types, sources, availability, price and major constraints in sourcing for non-conventional feed and feedstuff using a structured questionnaire system. The results of the survey showed that all respondents are male and married with crop farming as their primary occupation. 46.67% of the farmers had primary education with 6-10 years of livestock farming experience. The largest percentage (66.77%) of the farmers adopts intensive farming system. Feed resources were less expensive during harvest and expensive long after harvest i.e. during the dry season. High feed cost was the major constraints faced in sourcing feed. The feedstuffs were available from August to December and became relatively scarce in January. Respondents improve the nutritive value of the feedstuff by treating them with urea, sugarcane molasses and potassium. Farm residues, home remnants and agro allied waste were shown to have abetted the challenges of scarcity of ruminant feed especially during the dry season of the year. Some of the feedstuffs were not available at some periods of the month, a vivid picture of the time of their availability as shown in research could help the farmers to know when these feedstuffs are available and then buy at cheaper price and store for use at the time of scarcity. This will ultimately reduce cost of feeding and consequently, the cost of production.